2019
DOI: 10.3390/pharmaceutics11070343
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of EPR Effect and Efficacy of Anticancer Nanomedicine by Carbon Monoxide Generating Agents

Abstract: One obstacle to the successful delivery of nanodrugs into solid tumors is the heterogeneity of an enhanced permeability and retention (EPR) effect as a result of occluded or embolized tumor blood vessels. Therefore, the augmentation of the EPR effect is critical for satisfactory anticancer nanomedicine. In this study, we focused on one vascular mediator involved in the EPR effect, carbon monoxide (CO), and utilized two CO generating agents, one is an extrinsic CO donor (SMA/CORM2 micelle) and another is an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Only poorly vascularized tumors, mainly pancreatic, prostatic and liver metastatic experience less EPR effect than other types of cancer. Meda et al [ 132 ] discovered that substances that emulate the effect of vascular mediators involved in EPR effect could enhance it, principally nitric oxide (NO), as well as bradykinin, prostaglandins and VEGF, by facilitating tumor angiogenesis and growth. Recent developments have also demonstrated that another vascular mediator, carbon monoxide (CO), also enhances this EPR effect.…”
Section: Polymeric Nanoparticles In Oncologic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Only poorly vascularized tumors, mainly pancreatic, prostatic and liver metastatic experience less EPR effect than other types of cancer. Meda et al [ 132 ] discovered that substances that emulate the effect of vascular mediators involved in EPR effect could enhance it, principally nitric oxide (NO), as well as bradykinin, prostaglandins and VEGF, by facilitating tumor angiogenesis and growth. Recent developments have also demonstrated that another vascular mediator, carbon monoxide (CO), also enhances this EPR effect.…”
Section: Polymeric Nanoparticles In Oncologic Treatmentmentioning
confidence: 99%
“…It has been demonstrated that this effect was more present when the systolic blood pressure was higher than normal. In order to intensify the EPR effect, blood pressure can be elevated, or NO-releasing and CO-releasing agents can be administered [ 129 , 130 , 132 , 133 ]. It is important to mention that, with elevated blood pressure, studies showed that the accumulation of nanocarriers in the tumor was significantly higher and the release of these substances in healthy tissues was lower, due to vasoconstriction and compaction of endothelial junctions, translating in less toxicity [ 129 ].…”
Section: Polymeric Nanoparticles In Oncologic Treatmentmentioning
confidence: 99%
“…Similarly, carbon monoxide (CO) was utilized as a potential enhancer of the EPR effect. Recently, Fang et al employed two CO generating agents, either extrinsic CO donor micelle containing tricarbonyldichlororuthenium (II) dimer or endogenous CO donor using PEGylated hemin inducing heme oxygenase-1 [ 109 ]. It was proved that the agents induced the generation of CO selectively in solid tumors, thus enhanced the EPR effect leading to a two- to three-fold increased tumor accumulation of used nanomedicines.…”
Section: Augmentation Of the Passive Accumulation In Solid Tumorsmentioning
confidence: 99%
“…The use of nanoparticles as drug delivery systems is already a reality, with more than 50 nanomedicines approved by the Food and Drug Administration (USA) in April 2016, and more to come in the foreseeable future [ 1 ]. The use of nanoparticles as delivery systems may provide numerous benefits [ 2 , 3 , 4 ], including enhanced drug delivery to tumor cells [ 5 , 6 ], controlled release and improved biodistribution [ 7 ], all of which result in a reduction of drug side effects [ 8 , 9 ]. Among polymeric nanoparticles used as delivery systems, silk fibroin-based nanoparticles (SFN) from the silkworm Bombyx mori have shown promising results, partly due to their biodegradability, biocompatibility and nontoxicity [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%